Religious Tourism and Event Management: An Opportunity for Local Tourism Development - Cerutti, Stefania (The international journal of religious tourism and pilgrimage, 2015)
Religious events represent one of the ancient forms of encounter and should play an important role in enhancing tourism in the areas in which they take place. The aim of the study is to investigate the role of religious events as a key component of local tourism development. The adopted research methodology is primarily based on the gathering and interpretation of qualitative data. The paper considers small and medium sized religious events, analysing their event management process. It focuses on two case studies in northern Italy: the Devotional and Cultural Tourism Exchange of Oropa and the Passion Play of Sordevolo.